An insight into the use and advantages of Carbopol in topical mucoadhesive drug delivery system: A systematic review - Mohammad Hamdi, Nurul Ain; Azmi, Nurul Atifah; Mohd Sabari, Nurul Hanis; Harun @ Ismail, Ahmad Fahmi; Haris @ Harith, Muhammad Salahuddin (IIUM Press, 2023)
In recent years, mucoadhesive topical application of mucous membrane has gained considerable interest among formulation researchers in advanced drug delivery systems. It has been identified as a potential route for both local and systemic drug delivery. A mucoadhesive agent is usually incorporated in the formulation to overcome the disadvantages associated with the conventional topical formulation. These disadvantages include low residence time of the medication on the site of application due to tongue movement and salivary washout in the intraoral formulation, mucociliary clearance in the intranasal application, and rapid precorneal elimination in the intraocular formulation. Carbomer or known as Carbopol is a mucoadhesive polymer that is widely studied for topical delivery of pharmaceutical agents to the mucous membrane. The use of Carbopol and its advantages in the mucoadhesive topical application has gained considerable interest with several published studies and is available in various grades. In this study, a systematic review was performed on the available literature that investigates the Carbopol application in mucoadhesive topical drug delivery. A systematic searching strategy was performed in Scopus, ProQuest, and PubMed databases using predetermined search strings. A total of 778 articles were retrieved, however, only 25 articles met the inclusion criteria and were used for data synthesis. The results showed that incorporation of Carbopol as mucoadhesive polymer hold multiple advantages in drug delivery namely excellent mucoadhesion effect, the prolonged residence time of the formulation, enhanced drug permeation, prolonged release of drug, pseudoplastic behaviour of the formulation, pH compatibility with all mucosal site, and biocompatible.Conclusion: This suggests that the incorporation of Carbopol can be an effective mucoadhesive agent for topical drug delivery systems.